Klasifikasi Kategori Buku dengan menggunakan Metoda Naïve Bayes (Studi Kasus: Perpustakaan STKIP PGRI Sumatera Barat) - Pernanda, Anggri Yulio; Samudra, Ami Anggraini (Universitas (STKIP) PGRI Sumatera Barat, 2021)
The number of documents in the form of books, scientific articles, reports etc. is always increasing every day, this certainly makes it difficult for groups or types of documents to classify. Using the Naïve Bayes classifier, which is an approach that refers to the Bayes theorem, is a simple classification algorithm but has high accuracy. Naïve Bayes refers to previous knowledge which is strengthened in advance by processing the title text of a new document so that it can be used to facilitate the classification of new document classes. Based on the results of trials conducted using 125 training data on 10 test data in 5 class groups, the accuracy value is quite high, namely 90% correct classification.